1996
DOI: 10.1128/mcb.16.6.2870
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Regulation of the Spc1 Stress-Activated Protein Kinase in Schizosaccharomyces pombe

Abstract: Spc1, an osmotic-stress-stimulated mitogen-activated protein kinase (MAPK) homolog in the fission yeast Schizosaccharomyces pombe, is required for the induction of mitosis and survival in high-osmolarity conditions. Spc1, also known as Sty1, is activated by Wis1 MAPK kinase and inhibited by Pyp1 tyrosine phosphatase. Spc1 is most closely related to Saccharomyces cerevisiae Hog1 and mammalian p38 kinases. Whereas Hog1 is specifically responsive to osmotic stress, we report here that Spc1 is activated by multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
331
0
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(354 citation statements)
references
References 37 publications
18
331
0
5
Order By: Relevance
“…If cAPK has a similar role in S. pombe, pka1 mutants would be expected to have high constitutive levels of hsps, including also Tps1 (Blá zquez et al, 1994;Degols et al, 1996). In accordance with this assumption, it has recently been reported that the level of tps1 þ mRNA in an unconditioned pka1 mutant is about threefold higher than in the corresponding control strain (Ferná ndez et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…If cAPK has a similar role in S. pombe, pka1 mutants would be expected to have high constitutive levels of hsps, including also Tps1 (Blá zquez et al, 1994;Degols et al, 1996). In accordance with this assumption, it has recently been reported that the level of tps1 þ mRNA in an unconditioned pka1 mutant is about threefold higher than in the corresponding control strain (Ferná ndez et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…Notably, the deletion of Pmk1 MAPK, which regulates cell integrity (Toda et al, 1996;Sugiura et al, 1999Sugiura et al, , 2003, suppressed the temperature sensitivity of the cdc4-8 mutant cells ( Figure 6A, cdc4-8⌬pmk1). In contrast, the deletion of Spk1 MAPK, which regulates meiosis (Gotoh et al, 1993;Figure 6A, cdc4-8⌬spk1), or the deletion of Spc1/Sty1 MAPK, a homologue of p38 in fission yeast (Millar et al, 1995;Degols et al, 1996), did not suppress the temperature-sensitive growth of cdc4-8 mutant cells ( Figure 6A, cdc4-8⌬spc1). Thus, the deletion of Pmk1 specifically suppressed the temperature-sensitive phenotype of the cdc4-8 mutants, suggesting that the Pmk1 MAPK may phosphorylate Nrd1, thus controlling the function of Nrd1.…”
Section: Nrd1 Is a Direct Target Of Mapk Pmk1mentioning
confidence: 88%
“…MAPK pathway-induced expression of protein phosphatases is likely to be a general mechanism of adaptation. Expression of MSG5, a gene encoding a dual specificity phosphatase in S. cerevisiae, is induced by activation of the pheromone response pathway, and pyp2 ϩ , a gene encoding a PTP in S. pombe, is induced by an osmotic stress response pathway (15,19,20). Strains lacking pyp1 ϩ or pyp2 ϩ show a decreased rate of Sty1/Spc1-Tyr(P) dephosphorylation (19 -21).…”
Section: Resultsmentioning
confidence: 99%